Effects and dose-response relationships of resistance training on physical performance in youth athletes: a systematic review and meta-analysis - Lesinski, M.; Prieske, O.; Granacher, U. (British Journal of Sports Medicine, 2016)
Objectives To quantify age, sex, sport and training type-specific effects of resistance training on physical performance, and to characterise dose-response relationships of resistance training parameters that could maximise gains in physical performance in youth athletes.